Analysis of the senescence secretome during zebrafish retina regeneration - Konar, Gregory J.; Vallone, Kyle T.; Nguyen, Tu D.; Patton, James G. (Frontiers in Aging, 2025)
IntroductionZebrafish possess the innate ability to regenerate any lost or damaged retinal cell type with Müller glia serving as resident stem cells. Recently, we discovered that this process is aided by a population of damage-induced senescent immune cells. As part of the Senescence Associated Secretory Phenotype (SASP), senescent cells secrete numerous factors that can play a role in the modulation of inflammation and remodeling of the retinal microenvironment during regeneration. However, the identity of specific SASP factors that drive initiation and progression of retina regeneration remains unclear.Materials and MethodsWe mined the SASP Atlas and publicly available RNAseq datasets to identify common, differentially expressed SASP factors after retina injury. These datasets included two distinct acute damage regimens, as well as two chronic, genetic models of retina degeneration. We identified overlapping factors between these models and used genetic knockdown experiments, qRT/PCR and immunohistochemical staining to test a role for one of these factors (npm1a).ResultsWe discovered an overlapping set of 31 SASP-related regeneration factors across all data sets and damage paradigms. These factors are upregulated after damage with functions that span the innate immune system, autophagic processing, cell cycle regulation, and cellular stress responses. From among these, we show that depletion of Nucleophosmin 1 (npm1a) inhibits retina regeneration and decreases senescent cell detection after damage.DiscussionOur data suggest that differential expression of SASP factors promotes initiation and progression of retina regeneration after both acute and chronic retinal damage. The existence of a common, overlapping set of 31 factors provides a group of novel therapeutic targets for retina regeneration studies.